Virulence in murine model shows the existence of two distinct populations of Brazilian Vaccinia virus strains. - Jaqueline Maria Siqueira Ferreira; Betânia Paiva Drumond; Maria Isabel Maldonado Coelho Guedes; Marcelo Antônio Pascoal-Xavier; Camila Megale Almeida-Leite; Rosa Maria Esteves Arantes; Bruno Eduardo Fernandes Mota; Jônatas Santos Abrahão; Pedro Augusto Alves; Fernando Meireles Oliveira; Paulo César Peregrino Ferreira; Cláudio Antônio Bonjardim; et al. (PLoS ONE, 2008)
Brazilian Vaccinia virus had been isolated from sentinel mice, rodents and recently from humans, cows and calves during outbreaks on dairy farms in several rural areas in Brazil, leading to high economic and social impact. Some phylogenetic studies have demonstrated the existence of two different populations of Brazilian Vaccinia virus strains circulating in nature, but little is known about their biological characteristics. Therefore, our goal was to study the virulence pattern of seven Brazilian Vaccinia virus strains. Infected BALB/c mice were monitored for morbidity, mortality and viral replication in organs as trachea, lungs, heart, kidneys, liver, brain and spleen. Based on the virulence potential, the Brazilian Vaccinia virus strains were grouped into two groups. One group contained GP1V, VBH, SAV and BAV which caused disease and death in infected mice and the second one included ARAV, GP2V and PSTV which did not cause any clinical signals or death in infected BALB/c mice. The subdivision of Brazilian Vaccinia virus strains into two groups is in agreement with previous genetic studies. Those data reinforce the existence of different populations circulating in Brazil regarding the genetic and virulence characteristics.